Thirst, The shadow of death - Pike , Christopher (Simon pulse, London, 2011)
The Shadow of Death, the first book in Christopher Pike's The Last Vampire series. This supernatural thriller follows Alisa Perne, a 5,000-year-old vampire who has always outsmarted her adversaries. However, after being trapped in a new body, she faces challenges as the immortal race, the Telar, threatens to release a virus to decimate humanity. Alisa must turn to humans to help destroy the enemy.